Packaging bag for heat sterilization

The packaging bag with a laminate structure using specific acrylic polyol and silicon compound coatings addresses gas barrier deterioration and delamination issues, ensuring high transparency and durability under heat sterilization.

JP7661717B2Active Publication Date: 2025-04-15TOPPAN HOLDINGS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021024267
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-18
Publication Date
2025-04-15
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

Conventional packaging materials face issues with gas barrier properties deteriorating under harsh conditions like boiling and retort sterilization, transparency, metal detector compatibility, and environmental concerns, while metal foils and resin films have limitations such as delamination and material safety.

Method used

A packaging bag design comprising a laminate structure with a base film, primer layer, silicon oxide deposition layer, and gas barrier coating layer, where the primer layer contains specific acrylic polyol structures, and the gas barrier coating layer is formed by reacting silicon compounds with a water-soluble polymer, ensuring high gas barrier properties and resistance to delamination and swelling.

Benefits of technology

The packaging bag maintains excellent transparency, gas barrier properties, and resistance to tearing and delamination even after heat sterilization treatments, while being environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661717000008
    Figure 0007661717000008
  • Figure 0007661717000009
    Figure 0007661717000009
  • Figure 0007661717000001
    Figure 0007661717000001
Patent Text Reader

Abstract

To provide a packaging bag excellent in transparency to allow a content to be seen through, having high gas barrier properties while applicable to a metal detector, as well as capable of maintaining the high gas barrier properties even after a heat sterilization treatment, and unlikely to cause a breakage or delamination.SOLUTION: A packaging bag for heat sterilization is composed of a laminate with a base material film, a primer layer, a silicon oxide vapor deposition layer, a gas barrier coating layer and a heat fusion layer laminated in this order. The primer layer is formed by mutually reacting acrylic polyol including a repeating unit having a specific partial structure, isocyanate and a silane coupling agent. The gas barrier coating layer is formed by coating-drying a coating liquid including two kinds of silicon compounds or hydrolysate thereof and a water-soluble polymer having a hydroxy group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging bag using a transparent barrier film. [Background technology]

[0002] In recent years, packaging materials used for packaging food and non-food items such as medicines and electronic components need to be protected from the effects of oxygen, water vapor, and other gases that can deteriorate the contents and that permeate the packaging bag in order to prevent deterioration of the contents and maintain their functions and properties. Therefore, they are required to have gas barrier properties that can block these gases.

[0003] Conventionally, the gas barrier layer has mainly been made of a resin film such as a copolymer of polyvinyl alcohol and ethylene-vinyl, polyvinylidene chloride, or polyacrylonitrile, a plastic film coated with such a resin, or a metal foil made of a metal such as aluminum or a metal-deposited film of such a metal.

[0004] Also, as a gas barrier resin film, for example, a laminated film is known in which a coating layer is provided on a resin substrate by polycondensing a composition containing an alkoxysilane such as Si(O-CH3)4, a silane coupling agent such as epoxysilane, and polyvinyl alcohol by a sol-gel method (see Patent Document 1). However, since this coating layer is made of hydrogen bonds, it is easily swollen and dissolved by water. Therefore, the gas barrier property is easily deteriorated under harsh conditions such as boiling and retort treatment.

[0005] On the other hand, metal foils and metal-deposited films have excellent gas barrier properties, but they have problems such as the inability to see through the packaging bag to check the contents, the inability to use metal detectors for inspection, and the need to treat them as non-combustible waste when discarded. In addition, gas barrier resin films and films coated with gas barrier resins are highly temperature and humidity dependent and cannot maintain sufficient gas barrier properties. Furthermore, vinylidene chloride and polyacrylonitrile, which are used as gas barrier resins, may become raw materials for harmful substances when discarded or incinerated.

[0006] For this reason, for example, Patent Document 2 proposes a gas barrier packaging material in which a vapor deposition layer made of an inorganic compound is used as the first layer, and a gas barrier coating layer formed by applying a solution containing a metal alkoxide or tin chloride and a water-soluble polymer and drying the solution by heating is used as the second layer. This gas barrier packaging material exhibits high gas barrier properties, and is water-resistant and moisture-resistant, as well as having a certain degree of heat resistance. However, since the second coating layer of the gas barrier packaging material is formed by hydrogen bonding between a metal alkoxide hydrolyzate and a water-soluble polymer having a hydroxyl group, there is a problem that the coating layer swells and gas barrier properties such as water vapor barrier properties deteriorate when used as a packaging material that requires treatment such as boiling and retort sterilization. Such packaging material cannot be used even with a small amount of deterioration for packaging materials that require very high gas barrier properties, such as primary packaging bags for infusions.

[0007] Furthermore, in gas barrier packaging materials in which an inorganic oxide vapor deposition layer or a gas barrier coating layer is laminated to a substrate, if the adhesion is insufficient under harsh conditions such as boiling or retort treatment, delamination can occur between the substrate and the inorganic oxide vapor deposition layer, resulting in a poor appearance, or the gas barrier properties can be reduced in the areas where delamination occurs, causing deterioration of the contents. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 2556940 [Patent Document 2] Patent No. 2790054 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention is intended to solve the problems of the conventional technology as described above, and has an object to provide a packaging bag which is highly transparent to allow the contents to be seen through, has high gas barrier properties (oxygen barrier properties and water vapor barrier properties), and is not only applicable to metal detectors, but also maintains high gas barrier properties (oxygen barrier properties and water vapor barrier properties) even after heat sterilization treatment such as boiling and retort sterilization, and is resistant to tearing and delamination. [Means for solving the problem]

[0010] That is, a packaging bag for heat sterilization according to one embodiment of the present invention is a packaging bag for heat sterilization comprising a laminate in which a base film, a primer layer, a silicon oxide deposition layer, a gas barrier coating layer, and a heat seal layer are laminated in this order, and the primer layer has a partial structure represented by the following general formula (I) or (II): Or a partial structure derived from phenyl methacrylate The gas barrier coating layer is formed by reacting an acrylic polyol containing a repeating unit having the formula: with an isocyanate and a silane coupling agent, and the gas barrier coating layer is formed by applying and drying a coating liquid containing a silicon compound or a hydrolyzate or condensate thereof and a water-soluble polymer having a hydroxyl group, and the silicon compound contains the following two types of (a) to (b), and the (a) component and the (b) component are: 2 When converted to Si(OH)3 by mass, R 2 The solid content of Si(OH)3 is 1 to 50 mass% of the total solid content, and the (a) component is SiO2 and the (b) component is R 2 When converted to Si(OH)3 by mass, the solid content ratio is SiO2 / (R 2 Si(OH)3 + water-soluble polymer) is in the range of 100 / 100 to 100 / 30. [ka] In formula (I), Q A represents an ester bond as shown in the formula, R A teeth Selected from the group consisting of an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, a methoxy group, an ethoxy group, a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, and a halogen atom. represents a substituent, and n1 is 1 to 3 In this formula, * represents the bonding site to the remainder of the repeating unit, and ** represents the bonding site to the phenyl group in the formula. [ka] In formula (II), Q B teeth -CONR- (R represents a hydrogen atom or an alkyl group), an alkylene group having 1 to 4 carbon atoms, a urethane bond, an ether bond, and an ester bond represented by *-O-CO-** (** represents the bonding site with the phenyl group in formula (II)). represents a linking group or a single bond, R B teeth Selected from the group consisting of an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, a methoxy group, an ethoxy group, a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, and a halogen atom. represents a substituent, and n2 is 1 to 3 represents an integer, and * represents a bonding site with the remainder of the repeating unit. However, at least one R B represents a hydroxyl group. (a) A silicon compound represented by the following general formula (III) or a hydrolyzate thereof: Si(OR 1 )4…(III) In the general formula (III), R 1 represents CH3, C2H5, or C2H4OCH3. (b) A silicon compound represented by general formula (IV), or a hydrolyzate or condensate thereof: (R 2 Si(OR 3 )3)n…(IV) In the general formula (IV), R 2 represents an organic functional group, and R 3 represents CH3, C2H5, or C2H4OCH3, and n is 1 or more.

[0011] The partial structure represented by the general formula (I) or (II) in the acrylic polyol Or a partial structure derived from phenyl methacrylate It is preferable that the content of the repeating unit having the formula: is 2 mol % or more and 50 mol % or less based on all the repeating units of the acrylic polyol.

[0012] In addition, the repeating unit having the partial structure represented by general formula (I) or (II) may be any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer.

[0013] The acrylic polyol may have a partial structure represented by the general formula (I) or (II): Or a partial structure derived from phenyl methacrylate In addition to the repeating unit having the above formula, the copolymer may further contain a (meth)acrylate repeating unit having a linear or branched alkyl group having 1 to 5 carbon atoms on the side chain, and / or a (meth)acrylate repeating unit having a hydroxyl group other than a phenolic hydroxyl group on the side chain.

[0014] The acrylic polyol is preferably a partial structure represented by the general formula (I) or (II). Or a partial structure derived from phenyl methacrylate In addition to the repeating unit having the formula:

[0015] The acrylic polyol is preferably a partial structure represented by the general formula (I) or (II). Or a partial structure derived from phenyl methacrylate In addition to the repeating unit having the formula: Figure US08120633-20130323-C00002 ...

[0016] The component (b) is preferably a trimer 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate represented by the following general formula (V). (NCO-R 4 Si(OR 3 )3)3…(V) In the general formula (V), R 4 represents (CH2)n, R 3 represents CH3, C2H5, or C2H4OCH3. Also, n is 1 or more.

[0017] The gas barrier coating layer and the heat-sealing layer may be bonded together with an adhesive for dry lamination.

[0018] A polyamide film may be laminated between the gas barrier coating layer and the heat seal layer.

[0019] Moreover, the packaging bag for heat sterilization is preferably transparent. Effect of the Invention

[0020] Therefore, according to the present invention, it is possible to obtain a packaging bag which is not only excellent in transparency and has high gas barrier properties (oxygen barrier properties and water vapor barrier properties) and is applicable to metal detectors, but also has high gas barrier properties (oxygen barrier properties and water vapor barrier properties) even after heat sterilization treatment and is less likely to break or delaminate. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a cross-sectional explanatory view showing an example of a packaging material constituting the packaging bag of the present invention. [Diagram 2] FIG. 4 is a cross-sectional explanatory view showing another example of a packaging material constituting the packaging bag of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] As shown in Fig. 1, the packaging bag of the present invention is composed of a laminate in which a base film 1, a primer layer 2, a silicon oxide vapor deposition layer 3, a gas barrier coating layer 4, and a heat-sealing layer 5 are laminated in this order. The gas barrier coating layer 4 and the heat-sealing layer 5 can be bonded with an adhesive layer ad1 formed from an adhesive for dry lamination.

[0023] 2, the laminate according to the present invention may have a polyamide film 6 laminated between the gas barrier coating layer 4 and the heat-sealing layer 5. The gas barrier coating layer 4 and the polyamide film 6, and the polyamide film 6 and the heat-sealing layer 5 can be bonded by adhesive layers ad2 and ad3 formed from a dry lamination adhesive, respectively.

[0024] Next, the materials of the substrate film 1 and each of the layers 2 to 6 constituting the laminate of the present invention will be described together with the method of forming each layer.

[0025] Examples of the substrate film 1 used in the present invention include polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin films such as polyethylene and polypropylene, polystyrene films, polyamide films such as 6,6-nylon, polycarbonate films, polyacrylonitrile films, and engineering plastic films such as polyimide films. The substrate film 1 may be either stretched or unstretched, and is preferably one having mechanical strength and dimensional stability. In particular, films arbitrarily stretched in biaxial directions are preferably used. Furthermore, when used as a packaging material, polyamide films and polyester films are preferred in terms of cost, moisture resistance, packing suitability, texture, and disposability, and polyester films are more preferred. The substrate film 1 may contain various well-known additives and stabilizers, such as antistatic agents, plasticizers, lubricants, and antioxidants.

[0026] The thickness of the base film 1 is not particularly limited, but in consideration of suitability as a packaging material and processability, it is practically preferably 3 to 200 μm, more preferably 6 to 30 μm.

[0027] To improve adhesion, the surface of the substrate film 1 may be pretreated with corona treatment, plasma treatment, ozone treatment, etc. Furthermore, the surface of the substrate may be treated with chemicals, solvents, etc. In particular, plasma treatment is preferred because it strengthens adhesion between the substrate surface and the primer layer 2 to be laminated next.

[0028] Next, the acrylic polyol used in the primer layer 2 contains a repeating unit (hereinafter referred to as "repeating unit (A)") having a partial structure represented by the following general formula (I) or (II). [ka]

[0029] In formula (I), Q A represents an ester bond as shown in the formula, R A represents a substituent, n1 represents an integer of 1 to 5, * represents the bonding site to the remainder of the repeating unit, and ** represents the bonding site to the phenyl group in the formula.

[0030] R A Examples of the substituent represented by the formula include an alkyl group (e.g., an alkyl group having 1 to 5 carbon atoms), a cycloalkyl group (e.g., a cycloalkyl group having 3 to 6 carbon atoms), an alkoxy group (e.g., a methoxy group or an ethoxy group), a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, a halogen atom, and the like. As described above, n1 represents an integer of 1 to 5, and may be an integer of 1 to 3. When n1 is an integer of 2 or more, a plurality of R A may be the same or different.

[0031] [ka]

[0032] In formula (II), Q B Q in formula (I) A R represents a single bond or a linking group other than an ester bond represented by the formula: B represents a substituent, n2 represents an integer of 1 to 5, and * represents a bonding site with the remainder of the repeating unit. However, at least one R B represents a hydroxyl group.

[0033] Q B As mentioned above, Q A Q represents a single bond or a linking group other than an ester bond represented by the formula: AExamples of linking groups other than the ester bond represented by the formula (II) include -CONR- (R represents a hydrogen atom or an alkyl group), an alkylene group (e.g., an alkylene group having 1 to 4 carbon atoms), a urethane bond, an ether bond, and an ester bond represented by *-O-CO-** (** represents the bonding site with the phenyl group in formula (II)).

[0034] R B Examples of the substituent represented by the formula (I) include an alkyl group (e.g., an alkyl group having 1 to 5 carbon atoms), a cycloalkyl group (e.g., a cycloalkyl group having 3 to 6 carbon atoms), an alkoxy group (e.g., a methoxy group, an ethoxy group), a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, a halogen atom, etc. However, as described above, when at least one R B represents a hydroxyl group.

[0035] As described above, n2 represents an integer of 1 to 5, or may be an integer of 1 to 3. When n2 is an integer of 2 or more, a plurality of R B may be the same or different.

[0036] The repeating unit (A) may be any unit having a partial structure represented by the above-mentioned general formula (I) or (II), and may be, for example, a repeating unit derived from a (meth)acrylate-based monomer, a repeating unit derived from a (meth)acrylamide-based monomer, a repeating unit derived from an N-substituted maleimide-based monomer, or a repeating unit derived from a styrene-based monomer.

[0037] When the repeating unit (A) is a repeating unit derived from a (meth)acrylate monomer, examples of the (meth)acrylate monomer include 4-methoxyphenyl (meth)acrylate, 4-hydroxyphenyl (meth)acrylate, 2,6-di-tert-butylphenyl (meth)acrylate, 2,6-di-tert-butyl-4-methoxyphenyl (meth)acrylate, 2-tert-butyl-4-hydroxyphenyl (meth)acrylate, 3-tert-butyl-4-hydroxyphenyl (meth)acrylate, 2,6-di-tert-butyl-4-methylphenyl (meth)acrylate, 2-hydroxy-4-tert-butylphenyl (meth)acrylate, and 2,4-di-methyl-6-tert-butylphenyl (meth)acrylate.

[0038] When the repeating unit (A) is a repeating unit derived from a (meth)acrylamide monomer, examples of the (meth)acrylamide monomer include N-(4-hydroxyphenyl)(meth)acrylamide.

[0039] When the repeating unit (A) is a repeating unit derived from an N-substituted maleimide monomer, examples of the N-substituted maleimide monomer include 4-hydroxyphenylmaleimide and 3-hydroxyphenylmaleimide.

[0040] When the repeating unit (A) is a repeating unit derived from a styrene-based monomer, the styrene-based monomer may be, for example, α-methyl-p-hydroxystyrene.

[0041] In this embodiment, the acrylic polyol is preferably a di- or ternary copolymer further containing one or more repeating units different from the repeating unit (A). In this case, the content of the repeating unit (A) in the acrylic polyol is preferably in the range of 2 mol% to 50 mol% based on the total repeating units in the acrylic polyol. When the content of the repeating unit (A) in the acrylic polyol is 2 mol% or more, the thermal deterioration of the primer layer can be more effectively suppressed.

[0042] In addition, when the content of the repeating unit (A) in the acrylic polyol is 50 mol% or less, the occurrence of yellowing and cracking during heating can be suppressed while maintaining the effect of suppressing thermal deterioration of the primer layer. From the same viewpoint, the content of the repeating unit (A) in the acrylic polyol may be 2 mol% or more and 30 mol% or less, or 2 mol% or more and 20 mol% or less.

[0043] In the present embodiment, examples of repeating units (hereinafter referred to as "copolymerization components") that may be contained in the acrylic polyol when it is a copolymer and that are different from the repeating unit (A) include (meth)acrylate-based repeating units, olefin-based repeating units, halogen atom-containing repeating units, styrene-based repeating units, vinyl acetate-based repeating units, and vinyl alcohol-based repeating units.

[0044] Examples of the (meth)acrylate repeating unit that is a copolymerization component include a repeating unit derived from a (meth)acrylate monomer having a linear or branched alkyl group on the side chain, and a repeating unit derived from a (meth)acrylate monomer having a hydroxyl group (excluding phenolic hydroxyl groups) on the side chain.

[0045] Examples of the (meth)acrylate repeating units having a linear or branched alkyl group on the side chain include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, and isooctyl (meth)acrylate. Examples of monomer-derived components include 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, myristyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, and octadecyl (meth)acrylate. These may be used alone or in combination of two or more. Among the above, (meth)acrylate-based repeating units having a linear or branched alkyl group having 1 to 4 carbon atoms in the side chain can be preferably used.

[0046] Examples of the (meth)acrylic repeating unit having a hydroxyl group other than a phenolic hydroxyl group in the side chain include monomer-derived components such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0047] Examples of the olefin repeating unit that is a copolymerization component include components derived from olefin monomers such as ethylene, propylene, isoprene, butadiene, etc. These may be used alone or in combination of two or more.

[0048] Examples of the halogen atom-containing repeating unit that is a copolymerization component include components derived from monomers such as vinyl chloride, vinylidene chloride, etc. These may be used alone or in combination of two or more.

[0049] Examples of the styrene-based repeating unit that is a copolymerization component include components derived from styrene-based monomers such as styrene, α-methylstyrene, vinyltoluene, etc. These may be used alone or in combination of two or more.

[0050] The copolymer may have any of the following structures: random copolymer, alternating copolymer, block copolymer, and graft copolymer. If the copolymer has a random structure, the manufacturing process is easy. Therefore, the random copolymer is more preferable than other copolymers.

[0051] Radical polymerization can be used as a polymerization method for obtaining the copolymer. Radical polymerization is preferred because it is easy to produce industrially. Radical polymerization may be a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, a suspension polymerization method, or the like. For radical polymerization, it is preferred to use a solution polymerization method. By using the solution polymerization method, it is easy to control the molecular weight of the copolymer.

[0052] In the radical polymerization, the above-mentioned monomer may be diluted with a polymerization solvent, and then a polymerization initiator may be added to polymerize the monomer.

[0053] The polymerization solvent may be, for example, an ester-based solvent, an alcohol ether-based solvent, a ketone-based solvent, an aromatic solvent, an amide-based solvent, and an alcohol-based solvent. The ester-based solvent may be, for example, methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl lactate, and ethyl lactate. The alcohol ether-based solvent may be, for example, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, 3-methoxy-1-butanol, and 3-methoxy-3-methyl-1-butanol. The ketone-based solvent may be, for example, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. The aromatic solvent may be, for example, benzene, toluene, and xylene. The amide-based solvent may be, for example, formamide and dimethylformamide. The alcohol solvent may be, for example, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, s-butanol, t-butanol, diacetone alcohol, 2-methyl-2-butanol, etc. In addition, the above-mentioned polymerization solvent may be used alone or in combination of two or more kinds.

[0054] In the radical polymerization, the amount of the polymerization solvent used is not particularly limited, but when the total amount of the monomers is set to 100 parts by mass, the amount of the polymerization solvent used is preferably 1 part by mass or more and 1,000 parts by mass or less, and more preferably 10 parts by mass or more and 500 parts by mass or less.

[0055] The radical polymerization initiator may be, for example, a peroxide or an azo compound. The peroxide may be, for example, benzoyl peroxide, t-butyl peroxyacetate, t-butyl peroxybenzoate, and di-t-butyl peroxide. The azo compound may be, for example, azobisisobutyronitrile, azobisamidinopropane salt, azobiscyanovaleric acid (salt), and 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].

[0056] The amount of radical polymerization initiator used is preferably 0.0001 parts by mass or more and 20 parts by mass or less, more preferably 0.001 parts by mass or more and 15 parts by mass or less, and even more preferably 0.005 parts by mass or more and 10 parts by mass or less, when the total amount of monomers is set to 100 parts by mass. The radical polymerization initiator may be added to the monomer and polymerization solvent before the start of polymerization, or may be dropped into the polymerization reaction system. Dropping the radical polymerization initiator into the polymerization reaction system for the monomer and polymerization solvent is preferable in that heat generation due to polymerization can be suppressed.

[0057] The reaction temperature of the radical polymerization is appropriately selected depending on the type of radical polymerization initiator and polymerization solvent. From the viewpoint of ease of production and reaction controllability, the reaction temperature is preferably 60° C. or more and 110° C. or less.

[0058] Next, the isocyanate used in the primer layer 2 may have at least two or more NCO groups in the molecule. For example, as the monomeric isocyanate, aromatic isocyanates such as tolylene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI), aliphatic isocyanates such as hexamethylene diisocyanate (HDI), bisisocyanate methylcyclohexane (H6XDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (H12MDI), and aromatic aliphatic isocyanates such as xylene diisocyanate (XDI) and tetramethylxylylene diisocyanate (TMXDI) may be used. Polymers or derivatives of these monomeric isocyanates may also be used. Examples of the polymers or derivatives include trimer nurate type, adduct type reacted with 1,1,1-trimethylolpropane, and biuret type reacted with biuret. The isocyanate compound may be arbitrarily selected from the above-mentioned monomeric isocyanates, their polymers, derivatives, etc., and one type may be used alone or two or more types may be used in combination.

[0059] Next, examples of the silane coupling agent used in the primer layer 2 include those having an epoxy group such as 3-glycidoxypropyltrimethoxysilane, those having an amino group such as 3-aminopropyltrimethoxysilane, those having a mercapto group such as 3-mercaptopropyltrimethoxysilane, those having an isocyanate group such as 3-isocyanatepropyltriethoxysilane, etc. Furthermore, the silane coupling agent may be used alone or in combination of two or more types.

[0060] The thickness of the primer layer 2 is generally desirably in the range of 0.005 to 5 μm, more preferably 0.01 to 1 μm, after drying. If it is less than 0.01 μm, it is difficult to obtain a uniform coating film from the viewpoint of coating technology, and conversely, if it exceeds 1 μm, it tends to be uneconomical.

[0061] Next, the silicon oxide vapor deposition layer 3 can be formed by, for example, a vacuum deposition method. In order to improve the denseness and adhesion to the primer layer 2, the vapor deposition may be performed using a plasma assisted method or an ion beam assisted method. Furthermore, by using a reactive vapor deposition method in which the vapor deposition is performed while blowing in oxygen gas, the transparency of the silicon oxide vapor deposition layer 3 to be formed can be further improved.

[0062] It is desirable to determine the thickness of the silicon oxide vapor-deposited layer 3 taking into consideration its flexibility as well as its gas barrier properties. If the silicon oxide vapor-deposited layer 3 is too thin, it becomes difficult for it to fully function as a gas barrier layer. On the other hand, if the silicon oxide vapor-deposited layer 3 is too thick, it will not be able to maintain its flexibility due to residual stress, and there is a risk of cracks occurring due to external factors after film formation. A silicon oxide vapor-deposited layer 3 with a thickness in the range of 5 to 300 nm has sufficient gas barrier properties and flexibility. The thickness is preferably 10 to 300 nm.

[0063] Next, the gas barrier coating layer 4 is formed by hydrolyzing the components (a) and (b) by adding a water-soluble polymer to improve flexibility while maintaining the gas barrier property and further adding the component (b) to improve water resistance to form a coating liquid, applying the coating liquid to form a film, and drying by heating. It is possible to add a commonly known catalyst, such as tin chloride or acetylacetonate, to control the hydrolysis of the components (a) and (b). In addition, in consideration of adhesion to ink and adhesive, wettability, and prevention of cracks due to shrinkage, known additives such as isocyanate compounds, clay minerals such as colloidal silica and smectite, stabilizers, colorants, and viscosity adjusters can be added to the coating liquid within a range that does not impair the gas barrier property or water resistance. (a) A silicon compound represented by the following general formula (III) or a hydrolyzate thereof: Si(OR 1 )4…(III) In the general formula (III), R 1 represents CH3, C2H5, or C2H4OCH3. (b) A silicon compound represented by general formula (IV), or a hydrolyzate or condensate thereof: (R 2 Si(OR 3 )3)n…(IV) In the general formula (IV), R 2 represents an organic functional group, and R 3 represents CH3, C2H5, or C2H4OCH3, and n is 1 or more.

[0064] The component (a) is the main component of the gas barrier coating layer 4 and is a compound represented by the above general formula (III), such as tetramethoxysilane and tetraethoxysilane.

[0065] The water-soluble polymer improves the flexibility of the gas barrier coating layer 4, which is mainly composed of the component (a), while maintaining its gas barrier properties. For example, polyvinyl alcohol, starch, and celluloses can be preferably used. In particular, the gas barrier properties are best when polyvinyl alcohol (hereinafter referred to as PVA) is used in the coating agent of the present invention. This is because PVA is a polymer that contains the most hydroxyl groups in its monomer unit, and forms very strong hydrogen bonds with the hydroxyl groups of the metal alkoxide after hydrolysis. The PVA referred to here is generally obtained by saponifying polyvinyl acetate, and includes so-called partially saponified PVA, in which several tens of percent of acetate groups remain, and fully saponified PVA, in which only a few percent of acetate groups remain. The molecular weight of PVA has a wide variety of polymerization degrees, ranging from 300 to several thousand, but there is no problem with the effect regardless of the molecular weight. However, in general, PVA with a high saponification degree and a high molecular weight with a high polymerization degree is preferred because it has high water resistance.

[0066] Next, component (b) improves the water resistance of the gas barrier coating layer 4 and is a silicon compound represented by the above general formula (IV) or a hydrolyzate thereof.

[0067] As the component (b), the organic functional group R 2However, compounds having non-aqueous functional groups such as vinyl groups, epoxy groups, methacryloxy groups, ureido groups, and isocyanate groups can be used. Since the non-aqueous functional groups are hydrophobic, the water resistance is further improved.

[0068] However, the organic functional group (R 2 When the aryl group is a ureido group, the compound has a particular odor, and when the aryl group is an isocyanate group, there is a drawback in that the reactivity is high and the pot life is short.

[0069] In addition, the organic functional group R 2 When a compound having a 3-glycidoxypropyl group or a 2-(3,4-epoxycyclohexyl) group is used as the aryl group, these organic functional groups are hydrolyzed to give Si(OR 1 Since the epoxy silane compounds form hydrogen bonds with the organic functional groups (R 2 However, in the case of vinyl and methacryloxy, irradiation with ultraviolet light or electron beams is required during the manufacturing process, which increases the number of facilities and steps, and tends to result in higher costs.

[0070] On the other hand, when a trimer 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate represented by the following general formula (V) is used as component (b), these drawbacks are eliminated, water resistance is improved, and a decrease in gas barrier properties can be prevented. (NCO-R 4 Si(OR 3 )3)3…(V) (In the general formula (V), R 4 represents (CH2)n, R 3 represents CH3, C2H5, or C2H4OCH3, and n represents 1 or more.

[0071] That is, this 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate is a condensation product of 3-isocyanatepropylalkoxysilane, and although the isocyanurate part loses chemical reactivity by condensation, it is known that due to the polarity of the nurate part, it exhibits the same performance as 3-isocyanatepropylalkoxysilane before condensation. Therefore, by adding 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate, it is possible to prevent the gas barrier coating layer 4 from swelling with water and improve water resistance, as in the case of adding 3-isocyanatepropylalkoxysilane. In addition, while 3-isocyanatepropylalkoxysilane has high reactivity and low liquid stability, the nurate part is not water-soluble due to its polarity, but is easily dispersed in an aqueous liquid, can keep the liquid viscosity stable, and has water resistance equivalent to that of 3-isocyanatepropylalkoxysilane. Furthermore, the nurate part is not only water-resistant, but also has Si(OR 1 )4 Water-soluble polymers having hydroxyl groups are less likely to form holes in the barrier, which can prevent a decrease in gas barrier properties.

[0072] In addition, 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate may be produced by thermal condensation of 3-isocyanatepropylalkoxysilane, and may contain the raw material 3-isocyanatepropylalkoxysilane, but this does not cause any problems. More preferable is 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate. Methoxy groups have a fast hydrolysis rate, and those containing propyl groups can be obtained relatively cheaply, so 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is practically advantageous.

[0073] Next, component (a) and component (b) are mixed by mixing component (a) with SiO2 and component (b) with R. 2 When converted to Si(OH)3 by mass, R 2The solid content of Si(OH)3 is preferably 1 to 50 mass% based on the total solid content (the sum of components (a) and (b)). Within this range, the gas barrier coating layer 4 can obtain highly water-resistant gas barrier properties that do not deteriorate even in severe treatments such as boiling and retort sterilization. If it is less than 1 mass%, the water resistance effect tends to be reduced, and if it exceeds 50 mass%, the functional groups become holes in the gas barrier coating layer, so that the gas barrier properties tend to be reduced. To obtain better water resistance required for boiling and retort sterilization and high gas barrier properties, the solid content is more preferably 5 to 30 mass% based on the total solid content.

[0074] In addition, component (a) is replaced with SiO2 and component (b) is replaced with R 2 When converted to Si(OH)3 by mass, the solid content ratio is SiO2 / (R 2 If the ratio of Si(OH)3 + water-soluble polymer) is within the range of 100 / 100 to 100 / 30, not only the water resistance and high gas barrier properties required for boiling and retort sterilization treatments, but also the flexibility due to the coating flexibility when considered as a packaging material is sufficiently imparted, which is preferable.

[0075] The order of mixing these three components may be arbitrary. The effect will be obtained regardless of the order of mixing. When components (a) and (b) are not dispersed in the coating solution and exist as oil droplets, it is preferable to carry out hydrolysis as described above to finely disperse them. In particular, it is preferable to hydrolyze components (a) and (b) separately and then add them to the water-soluble polymer, as this will result in fine dispersion of SiO2 and Si(OR 1 ) This is desirable from the standpoint of the hydrolysis efficiency of 4.

[0076] There are no particular limitations on the thickness of the gas barrier coating layer 4 after drying, but a thickness of 0.01 to 50 μm is desirable since a thickness of more than 50 μm may lead to cracks being easily generated.

[0077] The gas barrier coating layer 4 can be formed by a conventional coating method, such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, etc.

[0078] The coating film can be dried by any method that applies heat to the gas barrier coating layer to drive off water molecules, such as hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, etc., or by combining two or more of these methods. This drying causes hydrolysis of components (a) and (b), forming a gas barrier coating layer 4 with gas barrier properties.

[0079] For example, a non-oriented polyolefin film can be used as the heat-sealing layer 5. The thickness of the film may be 5 to 300 μm, and is preferably 10 to 100 μm.

[0080] The heat-sealing layer 5 and the gas barrier coating layer 4 can be bonded together with an adhesive ad1 for dry lamination. The adhesive ad1 can be applied by roll coating, gravure coating, knife coating, dip coating, spray coating, or other coating methods. The amount of the adhesive ad1 applied is 0.1 to 5.0 g m 2 (Dry state) is preferable.

[0081] Next, the polyamide film 6 improves the pinhole resistance and impact resistance of the packaging bag, and for example, 6-nylon, 6,6-nylon, MXD nylon, etc. can be used. A biaxially oriented polyamide film is preferable, and the thickness may be 5 to 100 μm, and preferably 10 to 50 μm. This polyamide film 6 and the gas barrier coating layer 4 can be bonded with a dry lamination adhesive ad2. Also, the polyamide film 6 and the heat-sealing layer 5 can be bonded with a dry lamination adhesive ad3.

[0082] According to the present invention, a silicon compound is used as the metal alkoxide, and the gas barrier coating layer is made sufficiently insolubilized by reacting this with a water-soluble polymer having a hydroxyl group.

[0083] That is, silicon compounds are condensed after hydrolysis to form a ceramic film. However, silicon oxides are hard and prone to cracking due to distortion caused by volumetric shrinkage during condensation, so it is very difficult to form a thin, transparent, uniform condensate coating on a film. Therefore, by adding a polymer, the ceramic film can be made flexible and cracks can be prevented. However, even if the polymer is uniform to the naked eye, it is often microscopically separated into metal oxide and polymer parts, which easily become pores in the barrier, thereby reducing the gas barrier properties. Here, the pores in the barrier refer to the parts in the film that do not form a dense network and facilitate gas permeation.

[0084] By using a water-soluble polymer having hydroxyl groups as the polymer, the metal oxide can be effectively dispersed between the polymer and the polymer during condensation by utilizing the strong hydrogen bonds between the hydroxyl groups of the polymer and the hydroxyl groups of the hydrolysate of the metal alkoxide, thereby maintaining flexibility and exhibiting high gas barrier properties close to those of ceramics.

[0085] However, even in this case, the gas barrier coating layer made of the silicon compound and the water-soluble polymer is formed by hydrogen bonds, and therefore swells and dissolves in water.

[0086] Therefore, by reacting the silicon compound with the component (a) and the component (b), swelling of the gas barrier coating layer is prevented and water resistance is significantly improved. That is, the component (b) forms hydrogen bonds with the component of general formula (a) and the water-soluble polymer through hydrolysis, so that it is less likely to form holes in the barrier, and on the other hand, the organic functional group forms a network, which prevents the water-soluble polymer from swelling due to addition of water to the hydrogen bonds, thereby significantly improving water resistance. Therefore, the gas barrier coating layer 4 obtained by reacting the components (a) and (b) with the water-soluble polymer has excellent gas barrier properties and flexibility, as well as water resistance that can withstand heat sterilization treatment such as retort or boiling.

[0087] In addition, by providing the gas barrier coating layer in combination with the silicon oxide vapor deposition layer on the base film, even higher gas barrier properties can be obtained. Furthermore, since there is a primer layer between the base film and the silicon oxide vapor deposition layer, which is made of an acrylic polyol having a partial structure represented by general formula (I) or (II), there is no deterioration in oxygen permeability and laminate strength even after boiling sterilization and retort sterilization, and the vapor deposition layer is hardly peeled off from the base film. EXAMPLES

[0088] Example 1 A 12 μm thick polyester film was used as the base film 1, and a coating liquid containing an acrylic polyol containing 20 mol % of a partial structure derived from 4-hydroxyphenyl methacrylate, a TDI-based curing agent as an isocyanate, and γ-isocyanatepropyltrimethoxysilane as a silane coupling agent was applied to the base film 1, and the coating liquid was dried by heating to form a primer layer 2 having a thickness of 1 μm. Next, silicon oxide was vapor-deposited on the primer layer 2 to form a silicon oxide vapor-deposited layer 3 having a thickness of 200 nm. Next, a coating liquid containing tetramethoxysilane, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, and PVA was applied on the silicon oxide vapor-deposited layer 3, and the silicon compound was condensed by heating and drying to form a gas barrier coating layer 4 having a thickness of 1 μm. Hereinafter, this film will be referred to as a "silicon-based gas barrier film" in order to distinguish it from the film of the comparative example described later.

[0089] Next, an adhesive (Mitsui Chemicals, Inc. dry lamination adhesive, product name: A525) was applied to this silicon-based gas barrier film using a dry lamination machine, and a laminate was produced by bonding it to a 70 μm-thick polyolefin-based non-oriented co-extruded film (Mitsui Chemicals Tohcello, Inc., product name: RXC22) as a heat-sealing layer 5. Then, these laminates were stacked on top of each other and the periphery was heat-sealed to produce a three-sided bag for heat sterilization having a length of 125 mm and a width of 95 mm.

[0090] Example 2 A silicon-based gas barrier film and a three-sided bag for heat sterilization were produced in the same manner as in Example 1, except that a compound having a partial structure derived from phenyl methacrylate was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.

[0091] Example 3 A silicon-based gas barrier film and a three-sided bag for heat sterilization were produced in the same manner as in Example 1, except that a compound having a partial structure derived from 4-hydroxyphenyl methacrylamide was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.

[0092] Example 4 An adhesive (Mitsui Chemicals, Inc. dry lamination adhesive, product name: A525) was applied to the silicon-based gas barrier film of Example 1 using a dry lamination machine, and a 15 μm-thick polyamide film (Kojin Co., Ltd., product name: Bonyl W) was laminated thereon. Further, an adhesive (Mitsui Chemicals, Inc. dry lamination adhesive, product name: A525) was applied to the polyamide film using a dry lamination machine, and a 70 μm-thick polyolefin-based non-oriented co-extruded film (Mitsui Chemicals Tohcello Co., Ltd., product name: RXC22) was laminated thereon as a heat-sealing layer 5 to produce a laminate. Then, these laminates were stacked on top of each other, and the periphery was heat-sealed to produce a three-sided bag for heat sterilization having a length of 125 mm and a width of 95 mm.

[0093] Comparative Example 1 A silicon-based gas barrier film and a three-sided bag for heat sterilization were produced in the same manner as in Example 1, except that a compound having a partial structure derived from styrene was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.

[0094] Comparative Example 2 A silicon-based gas barrier film and a three-sided bag for heat sterilization were produced in the same manner as in Example 1, except that a compound having a partial structure derived from hydroxyethyl methacrylate was used as the acrylic polyol instead of the partial structure derived from 4-hydroxyphenyl methacrylate.

[0095] Comparative Example 3 In contrast to Example 1, aluminum oxide was vapor-deposited on the primer layer 2 to form an aluminum oxide vapor-deposited layer having a thickness of 200 nm. Next, a coating liquid containing a metal alkoxide and a water-soluble polymer having a hydroxyl group was applied onto this aluminum oxide vapor-deposited layer, and the metal alkoxide was condensed and dried by heating to form a gas barrier coating layer 4 having a thickness of 1 μm. Hereinafter, this film is referred to as an "aluminum-based gas barrier film."

[0096] Next, an adhesive (Mitsui Chemicals, Inc. dry lamination adhesive, product name: A525) was applied to this aluminum-based gas barrier film using a dry lamination machine, and a laminate was produced by bonding it to a 70 μm-thick polyolefin-based non-oriented co-extruded film (Mitsui Chemicals Tohcello, Inc., product name: RXC22) as a heat-sealing layer 5. Then, these laminates were stacked on top of each other and the periphery was heat-sealed to produce a three-sided bag for heat sterilization having a length of 125 mm and a width of 95 mm.

[0097] Comparative Example 4 An adhesive (Mitsui Chemicals, Inc. dry lamination adhesive, product name: A525) was applied to the aluminum-based gas barrier film using a dry lamination machine, and a 15 μm-thick polyamide film (Kojin Co., Ltd., product name: Bonyl W) was laminated thereon, and an adhesive (Mitsui Chemicals, Inc. dry lamination adhesive, product name: A525) was applied to the polyamide film using a dry lamination machine, and a 70 μm-thick polyolefin-based non-oriented co-extruded film (Mitsui Chemicals Tohcello Co., Ltd., product name: RXC22) was laminated thereon as a heat-sealing layer 5 to produce a laminate. The laminates were then stacked on top of each other and the periphery was heat-sealed to produce a three-sided bag for heat sterilization having a length of 125 mm and a width of 95 mm.

[0098] (evaluation) 50 ml of pure water was sealed in the three-sided bags for heat sterilization of Examples 1 to 4 and Comparative Examples 1 to 4, and retort sterilization was performed at a temperature of 130°C for 30 minutes using a retort treatment device (manufactured by Hisaka Works, Ltd., product name: RCS-40RTG.N).

[0099] The oxygen barrier property and water vapor barrier property were evaluated before and after retort sterilization as described below. The bag breaking strength after retort sterilization was evaluated by a pressure test and a drop test. Furthermore, the adhesion between the substrate and the inorganic vapor deposition layer was visually evaluated for the presence or absence of delamination after retort sterilization. These results are shown in Table 1.

[0100] The oxygen barrier property was evaluated by measuring the oxygen transmission rate using the Mocon method in accordance with JIS K7126 at a temperature of 30°C and a humidity of 70% RH. The water vapor barrier property was evaluated by measuring the oxygen transmission rate using the Mocon method in accordance with JIS K7129 at a temperature of 40°C and a humidity of 90% RH. In both cases, a lower value indicates better barrier property.

[0101] In the pressure test, a load of 80 kg was applied to the retort sterilized three-sided bags and held for one minute, and the number of bags that broke was counted. In the drop test, the retort sterilized three-sided bags were stored in a refrigerator at 5°C for 24 hours, and then dropped twice from a height of 80 cm so that the flat surface of the three-sided bag hit a concrete floor, and the number of bags that broke was counted. Each test had five samples, and "0 / 5" in the table means that not a single bag was broken.

[0102] The occurrence of delamination was observed by folding the sealed portion of the pouch 180° after retort sterilization. If the inorganic oxide vapor deposition layer was found to have delaminated from the base film as a result of visual observation, it was marked with ×, and if no delamination was found, it was marked with ○.

[0103] [Table 1]

[0104] As can be seen from the results of Table 1, in terms of the pressure test and drop test, there is no significant difference between Examples 1 to 4 and Comparative Examples 1 to 4. All of them have excellent bag-breaking strength. In addition, there is no significant difference between Examples 1 to 4 and Comparative Examples 1 to 4 in terms of the oxygen barrier properties before and after retort sterilization.

[0105] On the other hand, regarding the water vapor barrier property, the three-sided bags of Comparative Examples 3 to 4 were significantly degraded after retort sterilization, whereas the three-sided bags of Examples 1 to 4 and Comparative Examples 1 and 2 maintained high barrier property even after retort sterilization.

[0106] In the evaluation of delamination, in Comparative Examples 1 and 2, peeling between the substrate film and the inorganic oxide vapor-deposited layer was observed.

[0107] These results show that the packaging bag of the present invention maintains excellent bag breaking strength and oxygen barrier properties before and after retort sterilization, while also greatly improving the water vapor barrier properties after retort sterilization, and exhibits good adhesion between the substrate and the inorganic vapor deposition layer. [Industrial Applicability]

[0108] The present invention can be used for a packaging bag for heat sterilization. [Explanation of symbols]

[0109] 1. Base film 2 Primer layer 3. Silicon oxide deposition layer 4 Gas barrier coating layer 5 Heat-sealing layer 6 Polyamide film ad1,ad2,ad3 Adhesive

Claims

1. A packaging bag for heat sterilization comprising a laminate in which a base film, a primer layer, a silicon oxide deposition layer, a gas barrier coating layer, and a heat seal layer are laminated in this order, the primer layer is formed by reacting an acrylic polyol containing a repeating unit having a partial structure represented by the following general formula (I) or (II) or a partial structure derived from phenyl methacrylate, an isocyanate, and a silane coupling agent with each other, the gas barrier coating layer is formed by applying and drying a coating liquid containing a silicon compound or a hydrolysate or condensate thereof and a water-soluble polymer having a hydroxyl group; The silicon compound contains the following two types of compounds (a) and (b), and the components (a) and (b) are: 2 (b) component R 2 Si(OH) 3 When converted to mass, R 2 Si(OH) 3 The solid content of the composition is 1 to 50 mass % based on the total solid content, and the component (a) is SiO 2 (b) component R 2 Si(OH) 3 When converted to mass, the solid content ratio is SiO 2 / (R 2 Si(OH) 3 + water-soluble polymer) is in the range of 100 / 100 to 100 / 30. 【Chemistry 1】 In formula (I), Q A represents an ester bond as shown in the formula, R A represents a substituent selected from the group consisting of an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, a methoxy group, an ethoxy group, a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, and a halogen atom; n1 represents an integer of 1 to 3; * represents a bonding site to the remainder of the repeating unit; and ** represents a bonding site to the phenyl group in the formula. 【Chemistry 2】 In formula (II), Q B represents a linking group selected from the group consisting of -CONR- (R represents a hydrogen atom or an alkyl group), an alkylene group having 1 to 4 carbon atoms, a urethane bond, an ether bond, and an ester bond represented by *-O-CO-** (** represents the bonding site with the phenyl group in formula (II)), or a single bond, and R B represents a substituent selected from the group consisting of an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, a methoxy group, an ethoxy group, a hydroxyl group, an acetyl group, a nitro group, a cyano group, a carboxyl group, an amino group, an ester group, and a halogen atom, n2 represents an integer of 1 to 3, and * represents a bonding site with the remainder of the repeating unit. B represents a hydroxyl group. (a) A silicon compound represented by the following general formula (III) or a hydrolyzate thereof: Si (OR 1 ) 4 …(III) In the general formula (III), R 1 is CH 3 , C 2 H 5 , or C 2 H 4 OCH 3 Represents. (b) A silicon compound represented by general formula (IV), or a hydrolyzate or condensate thereof: (R 2 Si(OR 3 ) 3 )n…(IV) In the general formula (IV), R 2 represents an organic functional group; R 3 is CH 3 , C 2 H 5 , or C 2 H 4 OCH 3 In addition, n represents 1 or more.

2. The content of repeating units having the partial structure represented by the general formula (I) or (II) or a partial structure derived from phenyl methacrylate in the acrylic polyol is 2 mol% or more and 50 mol% or less with respect to all repeating units of the acrylic polyol. The heat sterilization packaging bag according to claim 1.

3. The repeating unit having the partial structure represented by the general formula (I) or (II) is any one of a repeating unit derived from a (meth)acrylate monomer, a repeating unit derived from a (meth)acrylamide monomer, and a repeating unit derived from an N-substituted maleimide monomer. The packaging bag for heat sterilization according to claim 1 or 2.

4. The acrylic polyol further contains, in addition to the repeating units having the partial structure represented by the general formula (I) or (II) or a partial structure derived from phenyl methacrylate, a (meth)acrylate-based repeating unit having a linear or branched alkyl group having 1 to 5 carbon atoms on a side chain, and / or a (meth)acrylate-based repeating unit having a hydroxyl group other than a phenolic hydroxyl group on a side chain. The packaging bag for heat sterilization according to any one of claims 1 to 3.

5. The acrylic polyol further contains an olefin-based repeating unit in addition to a repeating unit having a partial structure represented by the general formula (I) or (II) or a partial structure derived from phenyl methacrylate. The packaging bag for heat sterilization according to any one of claims 1 to 3.

6. The acrylic polyol further contains a halogen atom-containing repeating unit in addition to a repeating unit having a partial structure represented by the general formula (I) or (II) or a partial structure derived from phenyl methacrylate. The heat sterilization packaging bag according to any one of claims 1 to 3.

7. The packaging bag for heat sterilization according to claim 1, characterized in that the component (b) is a trimer 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate represented by the following general formula (V): (NCO-R 4 Si(OR 3 ) 3 ) 3 …(V) In the general formula (V), R 4 (CH 2 ) n, R 3 is CH 3 , C 2 H 5 , or C 2 H 4 OCH 3 In addition, n represents 1 or more.

8. 8. The packaging bag for heat sterilization according to claim 1, wherein the gas barrier coating layer and the heat-sealing layer are bonded together with an adhesive for dry lamination.

9. 8. The packaging bag for heat sterilization according to claim 1, further comprising a polyamide film laminated between the gas barrier coating layer and the heat seal layer.

10. The packaging bag for heat sterilization according to any one of claims 1 to 9, characterized in that it has transparency.

Citation Information

Patent Citations

  • Photosensitive resin composition, cured film, method for forming cured film, organic el display device and liquid crystal display device

    JP2011209679A

  • Gas barrier laminate film

    JP2016000464A

  • Gas barrier laminate and method for producing the same

    JP2017140820A

  • Barrier laminated film and method for manufacturing the same

    JP2556940B2

  • Gas barrier laminated film and packaging material using this laminated film

    JP2790054B2